Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) Untuk Penentuan Dosen Pembimbing Praktik Terbaik - Lita Sari Muchlis; Yaslinda Lizar; Ulfa Maria Aini; Asriwan Guci (JOSTECH Journal of Science and Technology, 2023)
This study tries to apply a decision-making method to find best practice work supervisors at a university. This hail is due to the need for evaluation in the implementation of student paractek work. The working principle of TOPSIS is a decision-making technique that has the ability to solve problems based on various criteria. The purpose of this research is to determine the best supervisor using the Similarity to ideal solution (TOPSIS) method. This study has recommended three best lecturers for practical work supervisors, namely: D1 lecturers (0.665590062), D4 lecturers (0.594856811), and D2 (0.478112102), out of ten Practical Work Supervisors who have been assessed, the best three are obtained to be appointed as the best Practical Work Supervisors at UIN Mahmud Yunus Batusangkar.